Fostering Knowledge Collaboration in Construction Projects: The Role of BIM Application - Jiajia Cheng; Lu Huang; Lixuan Jiang; Jianghong Chen; Wenwen Chen; Yuanping He (Buildings, 2023)
Knowledge collaboration is beneficial for project parties to assess valuable knowledge resources from others in order to enhance their competitive advantages. However, knowledge collaboration is hampered by the special project environment and temporary structure of construction projects. Based on relational contract theory, this study employs trust and relational norms as the two relational governance mechanisms for improving knowledge collaboration. Next, this study explores the effect of relational governance mechanisms on knowledge collaboration and the moderating role of the building information modelling (BIM) application level. We collected data from 166 responses in construction projects. Our results reveal that relational norms significantly impact knowledge collaboration, which is contrary to the effect of trust. Furthermore, the BIM application level has an interactive effect with relational norms, which improves knowledge collaboration. These findings reveal that the level of BIM application significantly affects the effectiveness of relational governance mechanisms. This study suggests that project managers should help project parties to develop BIM responsibilities in order to facilitate collaborative performance.